Long-term scientific impact revisited - Reia, Sandro M.; Fontanari, José F. (European physical journal plus, 2022)
Citation-based measures are widely used as quantitative proxies for subjective factors such as the importance of a paper or even the worth of individual researchers. Here we analyze the citation histories of 4669 papers published in journals of the American Physical Society between 1960 and 1968 and argue that state-of-the-art models of citation dynamics and algorithms for forecasting nonstationary time series are very likely to fail to predict the long-term (50 years after publication) citation counts of highly-cited papers using citation data collected in a short period (say, 10 years) after publication. This is so because those papers do not exhibit distinctive short-term citation patterns, although their long-term citation patterns clearly set them apart from the other papers. We conclude that even if one accepts that citation counts are proxies for the quality of papers, they are not useful evaluative tools since the short-term counts are not informative about the long-term counts in the case of highly-cited papers. GraphicAbstract